Insidensi dan Faktor Risiko Infeksi Luka Operasi pada Bedah Obstetri dan Ginekologi di Rumah Sakit - Farahdina Chairani; Ika Puspitasari; Rizka Humardewayanti Asdie (Faculty of Pharmacy, Universitas Gadjah Mada)
Surgical Site Infection (SSI) is a type of Healthcare-associated infections (HAIs) which caused postoperative morbidity. SSI is widely reported in developing countries with a combined incidence of 11.8 episodes per 100 surgical procedures. This study aimed to identify risk factors for SSI in patients undergoing obstetric and gynecological surgeries at Dr. Sardjito General Hospital Yogyakarta. Data collection was conducted retrospectively using patient’s medical records during the period of January 1, 2017 to December 31, 2018. A total of 102 patients underwent obstetric and gynecological surgeries in the study period. The incidence of SSI in the cross sectional study was 9.80%. Obstetric surgeries had a lower SSI incidence compared to gynecological surgeries (1.96% versus 7.84% respectively). The risk factors for SSI identified in the bivariate analysis were comorbidity (P= 0.03), concomitant surgery (OR 8.25), intraoperative blood loss (OR 0.51), perioperative blood transfusion (OR 18.6), and duration of prophylactic antibiotics (OR 1.22). The results of multivariate analysis showed a significant relationship between intraoperative blood loss and SSI (OR 0.038, CI 95% 0.002-0.761; P= 0.032). Incidence and risk factors from our retrospective study on obstetric and gynecological surgeries can be reported simultaneously. Some of the risk factors identified in this study can be helpful for SSI risk stratification in hospital.